Evaluasi Penggunaan Antibiotik Pada Pasien Infeksi Saluran Kemih Menggunakan Metode Gyssens Di Rumah Sakit Kota Batam - Oktaviani, Fifin; Putri, Lita Riastienanda; Candra, Heldi (Yayasan Jompa Research and Development, 2025)
Urinary tract infection (UTI) is one of the most common infections among hospitalized patients and requires appropriate antibiotic therapy to prevent resistance. Batam City, as an industrial city, has a large productive-age population and a dynamic lifestyle, including nightlife activities in the city center, which contribute to risk factors for UTI. This study aims to identify the pattern of antibiotic use and evaluate the rationality of antibiotic prescribing in UTI patients using the Gyssens method in the adult inpatient ward of a hospital in Batam City. This is an observational study with a descriptive cross-sectional design, using retrospective data from 68 adult inpatients diagnosed with UTI during the period of January–June 2024. The evaluation was conducted using the Gyssens method. The results showed that the most commonly used antibiotics in UTI cases were Levofloxacin (31%) and Ceftriaxone (26%). The analysis of antibiotic rationality using the Gyssens method revealed that 20.6% of antibiotic use fell into category 0 (rational use), while the rest were categorized as IIb (36.8%), IIa (14.7%), IIIb (23.5%), and IVa (4.4%).